2019
DOI: 10.3892/ijmm.2019.4328
|View full text |Cite
|
Sign up to set email alerts
|

miR-217 inhibits the migration and invasion of HeLa cells through modulating MAPK1

Abstract: MicroRNA (miR)-217 serves a pivotal role in the progression of colorectal cancer, renal cell carcinoma and glioma, however, the role of miR-217 in cervical cancer (CC) remains unclear. In the present study, the mechanism of miR-217 in cervical cancer was explored. The mRNA expression of miR-217 and mitogen-activated protein kinase 1 (MAPK1) were assessed using reverse transcription-quantitative polymerase chain reaction analysis. Cell Counting-Kit 8, wound-healing and Transwell assays were performed to detect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 40 publications
2
18
0
Order By: Relevance
“…These kinases are involved in genomic stability, DNA damage, cell cycle progression, and epithelial-mesenchymal transition (47)(48)(49)(50)(51). Moreover, these kinases affect tumor development and progression by regulating tumor cell migration, invasion, and apoptosis (52,53). In RCC, differentially expressed CXC chemokines may modulate genomic stability, DNA repair, cell cycle progression, and the epithelial-mesenchymal transition by regulating these kinases.…”
Section: Discussionmentioning
confidence: 99%
“…These kinases are involved in genomic stability, DNA damage, cell cycle progression, and epithelial-mesenchymal transition (47)(48)(49)(50)(51). Moreover, these kinases affect tumor development and progression by regulating tumor cell migration, invasion, and apoptosis (52,53). In RCC, differentially expressed CXC chemokines may modulate genomic stability, DNA repair, cell cycle progression, and the epithelial-mesenchymal transition by regulating these kinases.…”
Section: Discussionmentioning
confidence: 99%
“…miR-217 has been reported to have antitumor effects in multiple types of cancer ( 34 , 35 ). For example, miR-217 inhibits EMT transition by targeting PTPN14 in gastric carcinoma ( 36 ) and suppresses HeLa cell migration and invasion by regulating MAPK1 ( 37 ). The current study validated the binding between LINC00467 and miR-217, as well as their negative correlation in OS.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-217 inhibits MAPK1 and reduces cell viability, migration, and invasion while enhancing cell apoptosis. They have introduced miR-217 as a tumor suppressor gene in cervical cancer [27]. Another study found that miR-217 expression was different in normal pancreatic cells compared with pancreatic cancer cells.…”
Section: Discussionmentioning
confidence: 99%